A Sensor Network Approach to Managing Data Quality in Citizen Science - Wiggins, Andrea; Lagoze, Carl; Wong, Weng-Keen; Kelling, Steve (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
For most citizen science projects in which volunteers act as intelligent sensors, data quality cannot be determined through comparison to an objective ground truth nor through consensus. In this paper we discuss the approach implemented by eBird, based on strategies used in autonomous sensor networks, to address the challenge of establishing the accuracy of humans at the tasks of detection and identification.